Конторольный поцелуй: [роман] / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2004)
Экземпляры: Ф. 1 (20201120) / Инвентарный номер: 48143 / Цена: 27.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Д 67 / ГРНТИ: 17.82 / ББК: 84Р6